Rodent Area Prostriata Converges Multimodal Hierarchical Inputs and Projects to the Structures Important for Visuomotor Behaviors - Chen, Chang-Hui; Hu, Jin-Meng; Zhang, Shun-Yu; Xiang, Xiao-Jun; Chen, Sheng-Qiang; Ding, Song-Lin (Frontiers in Neuroscience, 2021)
Area prostriata is a limbic structure critical to fast processing of moving stimuli in far peripheral visual field. Neural substrates underlying this function remain to be discovered. Using both retrograde and anterograde tracing methods, the present study reveals that the prostriata in rat and mouse receives inputs from multimodal hierarchical cortical areas such as primary, secondary and association visual and auditory cortices and subcortical regions such as anterior and midline thalamic nuclei and claustrum. Surprisingly, the prostriata also receives strong afferents directly from the rostral part of the dorsal lateral geniculate nucleus. This shortcut pathway probably serves as one of the shortest circuits for fast processing of the peripheral vision and unconscious blindsight since it bypasses the primary visual cortex. The outputs of the prostriata mainly target presubiculum (including postsubiculum), pulvinar, ventral lateral geniculate nucleus, lateral dorsal thalamic nuclei, zona incerta as well as pontine and pretectal nuclei, most of which are heavily involved in subcortical visuomotor functions. Taken together, these results suggest that the prostriata is poised to quickly receive and analyze peripheral visual and other related information and timely initiates and modulates adaptive visuomotor behaviors, particularly in response to unexpected quickly looming threats.